Coronary Artery Bypass Grafting in Patients with Intracoronary Stent Related Complications - Siraj, Masoom; Hasan, Md Sharif (University Heart Journal, 2012)
Intracoronary stenting is an established modality of treatment to relieve narrowing of coronary arteries. Increasing use of stenting is bringing to light new complications. Here we present our experience with a newly emerging indication for surgical intervention for cardiac surgeons. This new indication is complications arising from intracoronary stents. Very little is available in the existing literature to guide the surgeon. We explain our rationale in doing things with two of our cases. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10213 UHJ 2011; 7(1): 56-58